Red de comunicación informática (network) UNMSM - UNCTAD - Lovera Dávila, Daniel (2002)
The project of the United Nations development account seeks to articulate holistic strategies that integrate the economic, environmental and social dimensions of sustainable development in countries that depend on their marketable natural resources (minerals, gas, oil) from Latin America and the Caribbean ( LAC). This technical report is the result of a careful exploration of the web pages and existing networks on social, environmental, cultural and economic issues, linked to the sustainable use of non-renewable natural resources, and raises the feasibility of establishing an integrated work network based on the need for a multidisciplinary approach to the subject. This computer communication network will disseminate knowledge and issues related to education, research, policy design and exchange of experiences; initially using the web servers of the Universidad Nacional Mayor de San Marcos in Lima (Peru), that of the Moa Metallurgical Mining Institute in Cuba and UNCTAD in Geneva (Switzerland); intertwined in real time where each one will function as principal and mirror at the same time to ensure the permanence and updating of the information.